SIXTY YEARS FROM NUREMBERG: WHAT PROGRESS FOR INTERNATIONAL CRIMINAL JUSTICE? - McCormack L H Timothy (Fakultas Hukum Universitas Trisakti, 2005)
The commencement of the Nuremberg Trials is one other major event of 1945. There is no question that in the period since the Nuremberg Trials opened on 19 November 1945 there has been tremendous development in international criminal law. The Nuremberg Trial also represented a major breakthrough for international criminal justice and promised much for the future. But, the Nuremberg Trial (and the Tokyo Trial as well) had own weaknesses in terms of the conduct of the legal process. In this paper, the author also explains the establishment of the Ad Hoc International Criminal Tribunals, International Criminal Court and Trials by the US Military Commission.